Venous capacitance and venous return in young adults with typical vasovagal syncope: a cross-sectional study. (27th September 2021) - Fish, Ely; Barak Lanciano, Sapir; Shavit, Itay; Palacci, Hagar; Chaiat, Chen; Avivi, Ishay; Haber Kaptsenel, Ella; Nussinovitch, Udi
Abstract : Vasovagal syncope (VVS) has a high prevalence in the general population and is associated with potential complications. There is limited information on the possible association between venous capacitance (VC) and venous return (VR), important determinants of preload and VVS. Since the tilt test was reported to yield a high rate of false positive results, the aim of this study was to evaluate whether abnormal VC and VR at baseline could predispose individuals to VVS. To this end, 88 young, healthy volunteers were recruited and classified to 26 (29.5%) who experienced typical VVS and 62 (70.5%) who did not. VC and VR were evaluated with a commercial device and plethysmography applied to the elevated legs. Maximum venous outflow (MVO), segmental venous capacitance (SVC) and MVO/SVC ratio were calculated and averaged. No significant differences between MVO (5.0±0.5 vs 5.6±0.8, p>0.05), SVC (6.0±0.5 vs 6.3±0.8, p>0.05) or MVO/SVC ratio (0.83±0.02 vs 0.86±0.03, p>0.05) were observed for the non-VVS and VVS volunteers, respectively. There was a significant association between a higher MVO and SVC values and a larger decrease in diastolic blood pressure with standing, although correlations were weak (R 2 =0.0582 and 0.0681, respectively). In conclusion, at baseline, VC and VR are not impaired in healthy volunteers with a history of VVS. It remains unknown if similar results would be found in patients with cardiovascular comorbidities. Also, the sensitivity of VC and VR evaluations to identify a predisposition for VVS following physiological provocations merits further study.